2016
DOI: 10.3390/rs8110898
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Post-Disturbance Forest Recovery in the Greater Yellowstone Ecosystem Analyzed Using Landsat Time Series Stack

Abstract: Forest recovery from past disturbance is an integral process of ecosystem carbon cycles, and remote sensing provides an effective tool for tracking forest disturbance and recovery over large areas. Although the disturbance products (tracking the conversion from forest to non-forest type) derived using the Landsat Time Series Stack-Vegetation Change Tracker (LTSS-VCT) algorithm have been validated extensively for mapping forest disturbances across the United States, the ability of this approach to characterize … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 88 publications
0
27
0
2
Order By: Relevance
“…e freely available Global Forest Change product over British Columbia (Hansen et al, 2013), indicates a total of 85,900 km 2 has been lost (including wildfire and forestry) and 43,800 km 2 has been gained, for a net forest cover change of -42,100 km 2 between 2000 and 2015. Forest disturbance, change attribution, and recovery mapping are common applications of FOSI (Hermosilla et al, 2015b;Zhao et al, 2016;Zhu et al, 2012). Researchers have also endeavoured to associate changes in forest health to changes observed across the spectrum of satellitebased remote sensing wavelengths (Meng et al, 2016).…”
Section: Nº02mentioning
confidence: 99%
See 1 more Smart Citation
“…e freely available Global Forest Change product over British Columbia (Hansen et al, 2013), indicates a total of 85,900 km 2 has been lost (including wildfire and forestry) and 43,800 km 2 has been gained, for a net forest cover change of -42,100 km 2 between 2000 and 2015. Forest disturbance, change attribution, and recovery mapping are common applications of FOSI (Hermosilla et al, 2015b;Zhao et al, 2016;Zhu et al, 2012). Researchers have also endeavoured to associate changes in forest health to changes observed across the spectrum of satellitebased remote sensing wavelengths (Meng et al, 2016).…”
Section: Nº02mentioning
confidence: 99%
“…Forest disturbance, change attribution, and recovery mapping are common applications of FOSI (Hermosilla et al, 2015b;Zhao et al, 2016;Zhu et al, 2012). Researchers have also endeavoured to associate changes in forest health to changes observed across the spectrum of satellitebased remote sensing wavelengths (Meng et al, 2016). Recent studies have shown evidence for the accurate mapping of grey- (Hart & Veblen, 2015) and green- (Foster et al, 2017) attack spruce stands using spectral indices, while others have shown evidence for the use of thermal remote sensing (Hais & Kučera, 2008).…”
Section: Nº02mentioning
confidence: 99%
“…The potentially variable duration of disturbance effect raises the possibility that our single-year representation of the disturbed category may be insufficient and additional effort should be made to track recovery through time. This is, currently, not a trivial matter since land cover will transition to a number of different states until it returns to a condition similar to pre-disturbance [61].…”
Section: Updated Land Cover Helps Yield Prediction: the Relationship mentioning
confidence: 99%
“…The widespread availability of data and methods that enable dense time series analyses allows for remote sensing to characterize vegetation recovery post-disturbance, including Wittenberg et al (2007), Bastos et al (2011), Kennedy et al (2012), Chu and Guo (2014), Griffiths et al (2014), Frazier et al (2015, Zhao et al (2016), Bartels et al (2016), and Yang et al (2017). All these studies used a variety of approaches to investigate forest recovery, and most have been focused on the spectral recovery of vegetation greenness, by using vegetation indices such as Normalized Difference Vegetation Index (NDVI), Enhanced Vegetation Index, Normalized Burn Ratio, and tasseled cap greenness (Pickell et al, 2016;Yang et al, 2017).…”
Section: Remote Sensing Approachmentioning
confidence: 99%